ENHANCING COMPLIANCE THROUGH DIGITAL REMINDER SERVICES: EVIDENCE FROM TRAFFIC TICKET ENFORCEMENT IN INDONESIAN PROSECUTION OFFICES - Gilbert Johan Martin Sinaga (PT Akselerasi Karya Mandiri, 2026)
This study examines the effectiveness of digital reminder services in improving compliance with fine payments and the retrieval of confiscated evidence in traffic ticket administration at the Kuantan Singingi District Attorney’s Office. The study addresses a persistent administrative challenge, namely low offender compliance, which contributes to evidence accumulation and operational inefficiencies. A quantitative evaluative approach was employed using a before–after design, based on monthly administrative data from 2024 (pre-implementation) and 2025 (post-implementation). The findings indicate substantial improvements in administrative performance following the implementation of the digital reminder system. The case resolution rate increased from 46.1% to 94.4%, while the fine payment rate rose from 57.1% to 93.7%. These improvements suggest that digital reminder services function as an effective behavioral intervention by reducing informational delays and prompting timely compliance. Furthermore, increased payment compliance is systematically associated with faster evidence retrieval, leading to a reduction in backlog accumulation and enhanced administrative efficiency. This study contributes to the literature by demonstrating the dual impact of digital reminder systems, not only in shaping individual compliance behavior but also in improving organizational-level administrative performance. The findings highlight that low-cost, scalable digital interventions can play a critical role in strengthening compliance-driven public service systems, particularly in enforcement-based administrative contexts.